pls somebody have to help me on the best way to simplify equations like these; $\displaystyle x^3-1 , x^4-1 $ thanks
Follow Math Help Forum on Facebook and Google+
They are expressions not equations. x^3-1 = (x-1)(x^2+x+1) x^4-1 = (x^2-1)(x^2+1) = (x-1)(x+1)(x^2+1)
Originally Posted by lawochekel pls somebody have to help me on the best way to simplify equations like these; $\displaystyle x^3-1 , x^4-1 $ thanks $\displaystyle x^n-1 =\begin{cases}\left(x^{n/2}-1\right)\left(x^{n/2}+1\right), & \text{if }n\text{ is even} \\(x-1)\cdot \displaystyle \sum_{i=0}^{n-1} x^i, & \text{if }n\text{ is odd}\end{cases}$
View Tag Cloud